Pregnancy characteristics and adverse outcomes in offspring of women with epilepsy: a prospective registry study from Mainland China - Li, Rui; Chen, Qian; Cao, Xing; Yan, Hua; Wang, Pei; Huang, Qun; Li, Xiaoyi; Chen, Fang; Li, Yangchao; Kong, Qingxia; Guo, Chonglun; Zhang, Qi; et al. (Frontiers in Neurology, 2023)
Objective This study aimed to explore the influencing factors of adverse outcomes in the offspring of women with epilepsy (WWE) and to analyze the changes brought about by the epilepsy knowledge popularization campaign in China (EKPCIC). Methods This nested case-control study focused on WWE and their offspring from a female epilepsy cohort in mainland China. From January 2009 to August 2022, WWE was prospectively enrolled in 32 study centers. This study aimed to observe the health outcomes of their offspring within 1 year of age. The main outcome measure assessed the health status of the offspring within their first year of age. We aimed to analyze the effects of seizures, anti-seizure medicines (ASMs), and a lack of folic acid supplementation on adverse outcomes in the offspring of WWE and to explore the changes in perinatal management and adverse outcomes of the offspring after dissemination of the EKPCIC in 2015. Additionally, subgroup analyses were conducted to compare seizure control during pregnancy between the valproate and non-valproate groups. Results In total, 781 pregnancies in 695 WWE were included, of which 186 (23.69%) had adverse outcomes. The National Hospital Epilepsy Severity Scale score, number of seizures, status epilepticus, ASM type, and valproate and folic acid doses were associated with a high risk of adverse outcomes. After the EKPCIC, the use of ASMs (P = 0.013) and folic acid (P < 0.001), the seizure-free rate during pregnancy (P = 0.013), and the breastfeeding rate (P < 0.001) increased, whereas the incidence of complications during pregnancy decreased (P = 0.013). However, there was no significant difference in the incidence of adverse outcomes between the analyzed offspring pre-/post-EKPCIC. Additionally, there was no association between the frequency of seizures at different time points during pregnancy and the use of valproate (F = 1.514, P = 0.221). Conclusion Possible factors influencing adverse outcomes in the offspring of WWE include seizures, type and number of ASM usage, and a lack of folic acid supplementation. Although the management of WWE during pregnancy is now more standardized, further efforts are needed to reduce adverse outcomes in offspring.